Sustainable Competitive Advantage: Examining Sustainable Advantage Through External and Organizational Environment with Vrio Analysis - Dela Cruz Angeline Kate, De Guzman, Ryan Joseph V., Dimaano Gerry Mae P., Rodaje, Jabez R., Tizon, Mark Vincent Jr C., Villamor, Mary Rose C. 4 0 16; 5 (2023)
ABSTRACT: This study aims to analyze the sustainable competitive advantage of coffee stores in Manila through a VRIO framework assessment of the effects of external factors and firm decisions. This study investigates the complex interplay between organizational and external environments, with a particular emphasis on sustainable and environmental aspects, sustainable practice awareness, and perception. In order to examine the important relationships among external factors, firm decisions, and the VRIO0 framework, hypotheses are developed. The research utilizes the Resource-Based View framework to emphasize the criticality of internal capabilities and resources in ascertaining a competitive edge. In order to collect insights from coffee shop managers, customers, and coffee farmers, a descriptive research design is implemented, incorporating survey questionnaires and adapted data analysis. The findings suggest that external variables have an insignificant impact on the sustainable competitive advantage of a coffee establishment. However, the VRIO framework is heavily influenced by permanent decisions, such as sustainability strategy and employee engagement. This study provides significant contributions to the coffee industry by highlighting the importance of adopting a nuanced strategic approach and directing internal attention toward capabilities in order to attain long-term sustainability. Keywords: Sustainable competitive advantage, VRIO analysis, external factors, firm choices, coffee industry, Manila, Resource-Based View.
Business Research: (BSBA major in Human Resource Management) - Pamantasan ng Lungsod ng Maynila, 2023.
Keywords: 2 -- 0; 6; 20; 20; 2